Influence of rotation speed on the steady cooling effects in the turbine disc cavity. (August 2019) - Chen, Shuxian; Liang, Zhenyu; Gu, Wei; Yuan, Weiqi
Abstract: The flow and heat transfer characteristics in the counter-rotating turbine disc cavity is numerically simulated using the rng k-ε turbulence model, and the influence of rotation speed on the steady flow and the cooling effects is further investigated. The results indicate that the influence of rotation speed in low speed range on the upstream disc surface heat transfer depends on the relative driving action of rotating radial force and intake inertial force on the flow near the upstream disc. With respect to the downstream disc, the convective heat transfer coefficient on the disc surface in the lower radius region decreases while the one in the higher radius region increases with the increase of rotation speed.